2011
DOI: 10.1007/s00330-011-2187-2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of hydro-multidetector row CT in the local T staging of oesophageal cancer compared to postoperative histopathological results

Abstract: Using the hydro-technique and applying specific assessment criteria, MDCT appears to be an accurate, non-invasive diagnostic tool for local tumour staging of oesophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 47 publications
0
20
2
4
Order By: Relevance
“…T-Staging: Die MDCT ist im T-Staging in den frühen Stadien limitiert. Dennoch können unter Verwendung der "Hydro-Technik" Sensitivitäten von 95 % und ein positiver prädiktiver Wert von 96 % erreicht werden [129]. Ein T-Staging konnte in dieser Studie bei bis zu 76 % der Fälle korrekt durchgeführt werden.…”
Section: Hintergrundunclassified
“…T-Staging: Die MDCT ist im T-Staging in den frühen Stadien limitiert. Dennoch können unter Verwendung der "Hydro-Technik" Sensitivitäten von 95 % und ein positiver prädiktiver Wert von 96 % erreicht werden [129]. Ein T-Staging konnte in dieser Studie bei bis zu 76 % der Fälle korrekt durchgeführt werden.…”
Section: Hintergrundunclassified
“…In addition, we evaluated the MDCT images at portal venous phase in this study. It has been reported that the arterial phase rather than the portal venous phase can improve the accuracy of T‐staging of esophageal cancer, especially early‐staged lesions . This should be confirmed which phase should be optimal in the assessment of the distance between the esophageal tumor and the aorta in the future.…”
Section: Discussionmentioning
confidence: 92%
“…T and N stage were analyzed as described previously [12]. Clinical tumor stage was assessed according to the TNM classification of the Union for International Cancer Control (UICC), 6 th edition [13].…”
Section: Resultsmentioning
confidence: 99%